Intermittent Fasting Exacerbates the Acute Immune and Behavioral Sickness Response to the Viral Mimic Poly(I:C) in Mice - Zenz, Geraldine; Jačan, Angela; Reichmann, Florian; Farzi, Aitak; Holzer, Peter (Frontiers in Neuroscience, 2019)
Intermitted fasting and other forms of calorie restriction are increasingly demonstrated to exert potential health benefits. Interestingly, restricted feeding is also able to mitigate sickness in response to bacterial factors stimulating Toll-like receptor 4 (TLR4). However, little is known about how fasting modifies the activity of virus-associated molecular patterns. We therefore analyzed the impact of an intermittent fasting regimen on the immune and behavioral response to the TLR3 agonist and viral mimic polyinosinic:polycytidylic acid (Poly(I:C)) in mice. The effects of intraperitoneally injected Poly(I:C) (12 mg/kg) on plasma and cerebral cytokine expression and behavior (locomotion, exploration and ingestion) were examined in male C57BL/6N mice under control conditions and following a 9-day period of intermittent (alternate day) fasting (IF). Poly(I:C) increased the circulating levels of cytokines (TNF-α, MCP-1, IL-6, IL-10, IFN-α, IFN-γ,), an effect amplified by IF. In addition, IF aggravated sickness behavior in response to Poly(I:C), while cerebral cytokine expression was enhanced by application with the viral mimic without any clear effect of the fasting regimen. Furthermore, IF augmented the expression of neuropeptide Y (NPY) mRNA in the hypothalamus and increased the plasma levels of corticosterone, while Poly(I:C) had little effect on these readouts. Our data show that IF does not abate, but exaggerates the immune and sickness response to the viral mimic Poly(I:C). This adverse effect of IF occurs despite increased hypothalamic NPY expression and circulating corticosterone levels, two factors known to have anti-inflammatory activity. We therefore propose that the effects of IF on the immune and behavioral responses to viral and bacterial factors are subject to different neuronal and neuroendocrine control mechanisms.